Flat high-elasticity high-temperature thermal insulation ceramic fiber and preparation method thereof
By combining electrospinning and pioneer transformation, hafnium acetylacetonate was introduced to prepare a flat silicon carbide ceramic fiber with high elasticity and hafnium-containing element, which solved the brittleness and oxidation failure problems of traditional ceramic fibers in high temperature environments, achieved excellent mechanical and oxidation resistance, and enhanced its application potential in high-temperature structural parts and aerospace fields.
Patent Information
- Application Number
- CN202510200172.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-24
- Publication Date
- 2025-03-25
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Traditional ceramic fibers are susceptible to oxidation under high temperature and high stress and severe thermal oxidation environments, causing material failure, and lack plastic deformation capabilities, showing significant brittleness, which limits its wide application in high-temperature structural parts and aerospace fields.
By combining electrospinning and pioneer transformation, the material structure design is optimized and the refractory metal (hafnium acetylacetonate) with excellent oxidation resistance is introduced to prepare a flat silicon carbide ceramic fiber with high elasticity containing hafnium elements.
It has achieved excellent mechanical properties, good heat insulation and high temperature resistance of ceramic fibers, as well as excellent oxidation resistance, and can maintain a residual amount of more than 80% under ablation environment of 1600°C, significantly improving its application potential in high-temperature structural parts and aerospace fields.
Smart Images

Figure CN119684006A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of ceramic fibers, and in particular, relates to a ceramic fiber and a preparation method thereof. Background Art
[0002] Ceramic fiber is considered to be a new type of thermal protection material with great potential due to its low density, high melting point, high strength and good oxidation resistance. It is widely used in high-temperature structural parts, aerospace and other cutting-edge technology fields. However, during high-speed flight, the leading edge, wings and other parts of the aerospace vehicle will rub against the atmospheric airflow to generate heat energy, and the intense friction causes the fuselage to withstand extremely high heat environment. According to relevant reports, when the flight speed of a supersonic aircraft reaches Mach 8, the temperature of its end is as high as 1800 ℃, and the surface temperature will exceed 3100 ℃. As the speed of the warhead increases, the aerodynamic heat energy is even greater, and the environment faced by the fuselage is more extreme. In the face of the above situation, high-temperature structural parts and the aerospace field have put forward more stringent standards and requirements for the lightweight, high strength, ultra-high temperature tolerance and oxidation resistance of thermal protection materials. However, due to its low fracture toughness, traditional ceramic fiber materials are very susceptible to oxidation in high temperature, high stress and harsh thermal oxidation environments, resulting in material failure. In addition, due to the bonds and characteristics of its molecular structure, ceramic fibers lack plastic deformation ability and show significant brittleness, which seriously affects their application as structural materials. Therefore, improving the high temperature resistance, oxidation resistance and mechanical properties of ceramic fibers has become a necessary condition for their use as high temperature structural materials in harsh environments.
[0003] In order to improve the high-temperature stability of ceramic fibers, scientists have made a lot of efforts, such as coating the surface of SiC ceramic-based composites to prevent oxygen from entering the material to improve its oxidation resistance. In addition, researchers have also studied the addition of oxidation inhibitors to the SiC matrix or reinforcement phase. These oxidation inhibitors will generate or become molten oxides in a high-temperature aerobic environment and adhere to the fiber surface, or fill in the cracks on the surface of the matrix or reinforcement phase, blocking oxygen from further entering the matrix or reinforcement phase, achieving an antioxidant effect. Although the above measures have improved the high-temperature oxidation resistance of the material to a certain extent, the inherent brittleness of ceramic fibers still limits their further application. In view of this, there is an urgent need to develop a new type of ceramic fiber with excellent mechanical strength and excellent oxidation resistance in high-temperature extreme environments to promote its wide application in high-temperature structural parts, aerospace and other fields. Summary of the invention
[0004] In order to solve the common problems of poor mechanical properties and easy high-temperature oxidation failure of traditional ceramic fibers, the present invention provides a flat high-elasticity high-temperature insulating ceramic fiber and a preparation method thereof. By optimizing the material structure design and introducing refractory metals with excellent antioxidant properties, the mechanical properties and high-temperature performance of the ceramic fiber in an aerobic environment are effectively improved. The ceramic fiber can be widely used in locations such as the leading edge of the wing or combustion system of an aircraft.
[0005] In order to achieve the above object, the present invention adopts the following technical solutions:
[0006] According to one aspect of the present invention, there is provided a flat high-elasticity high-temperature thermal insulation ceramic fiber, which is obtained by the following preparation method:
[0007] (1) dissolving polycarbosilane powder in tetrahydrofuran and stirring evenly, and then adding hafnium acetylacetonate to prepare a precursor solution; wherein the mass ratio of the polycarbosilane powder to the tetrahydrofuran is 2:(8-10), and the mass fraction of the hafnium acetylacetonate to the tetrahydrofuran is 5%-7%;
[0008] (2) adding a spinning aid cellulose acetate to the precursor solution to obtain an electrospinning solution;
[0009] (3) placing the electrospinning solution on an electrospinning machine for electrospinning to obtain nanofibers;
[0010] (4) After the nanofibers are cross-linked and solidified, they are calcined in a vacuum atmosphere or an inert atmosphere to remove organic components to obtain flat ceramic fibers.
[0011] According to another aspect of the present invention, there is provided a method for preparing a flat high-elasticity high-temperature thermal insulation ceramic fiber, comprising:
[0012] (1) dissolving polycarbosilane powder in tetrahydrofuran and stirring the mixture evenly, and then adding hafnium acetylacetonate to prepare a precursor solution;
[0013] (2) adding a spinning aid cellulose acetate to the precursor solution to obtain an electrospinning solution;
[0014] (3) placing the electrospinning solution on an electrospinning machine for electrospinning to obtain nanofibers;
[0015] (4) After the nanofibers are cross-linked and solidified, they are calcined in a vacuum atmosphere or an inert atmosphere to remove organic components to obtain flat ceramic fibers.
[0016] In the above-mentioned flat high-elasticity high-temperature thermal insulation ceramic fiber and its preparation method:
[0017] Furthermore, in step (1), the stirring time of dissolving the polycarbosilane powder in the tetrahydrofuran is 2 to 4 hours.
[0018] Furthermore, the stirring time of adding the hafnium acetylacetonate to obtain the precursor solution in step (1) is 1 to 5 hours.
[0019] Furthermore, the mass ratio of the cellulose acetate in step (2) to the tetrahydrofuran in step (1) is (5-7):100, and the stirring time of adding the spinning aid cellulose acetate to the precursor solution to obtain the electrospinning solution is 2-3 h.
[0020] Furthermore, the process parameters of the electrospinning in step (3) include: voltage of 10-20 kV, drum speed of 80-150 rpm, receiving distance of 15-20 cm, and feeding speed of 1-5 mL / h.
[0021] Furthermore, the cross-linking and curing in step (4) is carried out at 240-260° C. for 1-2 h.
[0022] Furthermore, the heating rate of the cross-linking curing is 1 to 5°C / min.
[0023] Furthermore, the calcination in step (4) is performed by heating to 1200° C. to 1400° C. and then keeping the temperature for 1 to 2 hours.
[0024] Furthermore, the heating rate of the calcination is 4 to 6 °C / min.
[0025] The beneficial effects of the present invention are:
[0026] (I) The flat high-elasticity high-temperature thermal insulation ceramic fiber prepared by the present invention has excellent mechanical properties: under the action of the high-voltage electric field force of electrospinning, the spinning solution droplets break into fine droplets and are stretched into fibers with a flat structure; the flat structure gives it a larger surface area, enhances the interaction force between fibers, helps the fiber maintain a stable shape when subjected to external forces, effectively disperses and transmits stress, avoids fracture or plastic deformation caused by stress concentration, and makes the ceramic fiber have excellent flexibility and elastic recovery ability.
[0027] (II) The flat high-elasticity high-temperature thermal insulation ceramic fiber prepared by the present invention has good thermal insulation and high temperature resistance: its thermal conductivity is as low as 0.039 W·m -1 ·K -1 , having good thermal insulation effect; in addition, compared with traditional silicon carbide ceramic fibers, the flat ceramic fibers containing hafnium elements of the present invention have a weight loss rate of less than 20% after ablation at up to 1600°C, and have good high temperature resistance.
[0028] (III) The flat high-elasticity high-temperature thermal insulation ceramic fiber prepared by the present invention has excellent oxidation resistance: the addition of hafnium not only improves the high-temperature resistance of the ceramic fiber, but also forms a crystalline protective film and a non-static boundary on the fiber surface. After sintering in an air atmosphere, the HfSiO4 becomes more resistant to high temperatures and greatly improves its oxidation resistance.
[0029] In summary, the present invention adopts a method combining electrospinning and precursor conversion, optimizes the material structure design and introduces a refractory metal (hafnium acetylacetonate) with excellent antioxidant properties to prepare a highly elastic flat silicon carbide ceramic fiber containing hafnium elements, solves the technical bottleneck of existing ceramic materials, and obtains excellent flexibility and elastic recovery. The hafnium-containing ceramic fiber of the present invention has a residual amount of more than 80% after ablation at up to 1600°C; compared with the residual amount of less than 60% of pure PCS fiber, the hafnium-containing ceramic fiber has a very high residual amount and has a lower thermal conductivity, good thermal stability and thermal insulation performance; when the carbonization temperature is 1400°C, a large number of microcrystalline structures are wrapped in the peripheral amorphous matrix, forming a large number of amorphous boundaries. The existence of amorphous boundaries better protects the matrix and improves the material's antioxidant and high temperature resistance. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 A flow chart of the preparation of the flat ceramic fiber provided by the present invention;
[0031] Figure 2 The scanning electron microscope images of the ceramic fibers prepared in Examples 1 to 3 of the present invention;
[0032] Figure 3 The scanning electron microscope image and its magnified image of the ceramic fiber prepared in Example 7 of the present invention;
[0033] Figure 4 The Fourier transform infrared spectra of the ceramic fibers prepared in Example 1 and Comparative Example 1 of the present invention are shown in FIG.
[0034] Figure 5 X-ray diffraction patterns of ceramic fibers prepared in Examples 1, 5-7 of the present invention;
[0035] Figure 6 TEM image of the ceramic fiber prepared in Example 7 of the present invention;
[0036] Figure 7 is the XRD pattern of the ceramic fiber prepared in Example 7 of the present invention;
[0037] Figure 8 Thermogravimetric curves of the fibers prepared in Example 1 and Comparative Example 1 of the present invention and thermal conductivity images of the ceramic fibers prepared in Examples 4-7; DETAILED DESCRIPTION
[0038] like Figure 1 As shown, the present invention provides a flat high-elasticity high-temperature thermal insulation ceramic fiber and a preparation method thereof, which are obtained according to the following steps:
[0039] (1) After dissolving polycarbosilane powder in tetrahydrofuran and stirring evenly, hafnium acetylacetonate is added to prepare a precursor solution; wherein the mass ratio of the polycarbosilane powder to the tetrahydrofuran is 2:(8-10), and the mass fraction of the hafnium acetylacetonate in the tetrahydrofuran is 5%-7%.
[0040] In some preferred embodiments of the present invention, the stirring time of dissolving the polycarbosilane powder in the tetrahydrofuran is 2 to 4 h; and the stirring time of adding the hafnium acetylacetonate to obtain the precursor solution is 1 to 5 h.
[0041] (2) Adding the spinning aid cellulose acetate into the precursor solution to obtain an electrospinning solution.
[0042] In some preferred embodiments of the present invention, the mass ratio of cellulose acetate to tetrahydrofuran is (5-7):100, and the stirring time of adding the spinning aid cellulose acetate to the precursor solution to obtain the electrospinning solution is 2-3 h.
[0043] (3) Placing the electrospinning solution on an electrospinning machine for electrospinning to obtain nanofibers.
[0044] In some preferred embodiments of the present invention, the process parameters of electrospinning include: voltage of 10-20 kV, drum speed of 80-150 rpm, receiving distance of 15-20 cm, and feeding speed of 1-5 mL / h.
[0045] (4) After the nanofibers are cross-linked and solidified, they are calcined in a vacuum atmosphere or an inert atmosphere to remove organic components, thereby obtaining hafnium-containing silicon carbide ceramic fibers having a flat structure.
[0046] In some preferred embodiments of the present invention, the cross-linking and curing is to place the nanofibers in an oven, heat the temperature to 240-260°C at a heating rate of 1-5°C / min, and then keep it warm for 1-2 hours; the calcination process is to place the cross-linked and cured polymer fibers in an atmosphere furnace, heat the temperature to 1200°C-1400°C at a heating rate of 4-6°C / min in a vacuum atmosphere or an inert atmosphere, and then continue for 1-2 hours.
[0047] To make the solutions and advantages of the present invention clearer, the present invention and its advantages are described in detail below in conjunction with specific implementation methods and the accompanying drawings, but the implementation methods of the present invention are not limited thereto.
[0048] Example 1
[0049] The silicon carbide ceramic fiber containing hafnium element is prepared according to the following steps:
[0050] (1) Dissolve 10 g of solid PCS in 50 g of tetrahydrofuran (THF) and stir thoroughly with a magnetic stirrer for 2 h until the liquid is clear. Add 2.5 g of hafnium acetylacetonate (Hf(acac)4) to the above transparent mixed solution and stir magnetically at room temperature for 2 h until it is completely dissolved.
[0051] (2) At room temperature, add 3.5 g of cellulose acetate to the solution prepared in step (1) and stir for 2 h until the solution becomes clear to obtain a spinning solution.
[0052] (3) The mixed spinning solution prepared in step (2) is sucked into a syringe and placed on an electrospinning machine. The voltage of the electrospinning machine is set to 15 kV, the flow rate to 3 mL / hr, the drum speed to 120 r / min, and the receiving distance to 15 cm.
[0053] (4) The prepared raw fibers were cross-linked and cured at 250 °C for 2 h to obtain polymer fibers.
[0054] Example 2
[0055] The silicon carbide ceramic fiber containing hafnium element is prepared according to the following steps:
[0056] (1) Dissolve 10 g of solid PCS in 50 g of tetrahydrofuran (THF) and stir thoroughly with a magnetic stirrer for 2 h until the liquid is clear. Add 3.5 g of hafnium acetylacetonate (Hf(acac)4) to the above transparent mixed solution and stir magnetically at room temperature for 2 h until it is completely dissolved.
[0057] (2) At room temperature, add 3.5 g of cellulose acetate to the solution prepared in step (1) and stir for 2 h until the solution becomes clear to obtain a spinning solution.
[0058] (3) The mixed spinning solution prepared in step (2) is sucked into a syringe and placed on an electrospinning machine. The voltage of the electrospinning machine is set to 14 kV, the flow rate to 4 mL / hr, the drum speed to 120 r / min, and the receiving distance to 15 cm.
[0059] (4) The prepared raw fibers were cross-linked and cured at 250 °C for 2 h to obtain polymer fibers.
[0060] Example 3
[0061] The silicon carbide ceramic fiber containing hafnium element is prepared according to the following steps:
[0062] (1) Dissolve 10 g of solid PCS in 50 g of tetrahydrofuran (THF) and stir thoroughly with a magnetic stirrer for 2 h until the liquid is clear. Add 5 g of hafnium acetylacetonate (Hf(acac)4) to the above transparent mixed solution and stir magnetically at room temperature for 2 h until it is completely dissolved.
[0063] (2) At room temperature, add 3.5 g of cellulose acetate to the solution prepared in step (1) and stir for 2 h until the solution becomes clear to obtain a spinning solution.
[0064] (3) The mixed spinning solution prepared in step (2) is sucked into a syringe and placed on an electrospinning machine. The voltage of the electrospinning machine is set to 17 kV, the flow rate to 3 mL / hr, the drum speed to 120 r / min, and the receiving distance to 15 cm.
[0065] (4) The prepared raw fibers were cross-linked and cured at 250 °C for 2 h to obtain polymer fibers.
[0066] Example 4
[0067] The silicon carbide ceramic fiber containing hafnium element is prepared according to the following steps:
[0068] (1) Dissolve 10 g of solid PCS in 50 g of tetrahydrofuran (THF) and stir thoroughly with a magnetic stirrer for 2 h until the liquid is clear. Add 2.5 g of hafnium acetylacetonate (Hf(acac)4) to the above transparent mixed solution and stir magnetically at room temperature for 2 h until it is completely dissolved.
[0069] (2) At room temperature, add 3.5 g of cellulose acetate to the solution prepared in step (1) and stir for 2 h until the solution becomes clear to obtain a spinning solution.
[0070] (3) The mixed spinning solution prepared in step (2) is sucked into a syringe and placed on an electrospinning machine. The voltage of the electrospinning machine is set to 15 kV, the flow rate to 3 mL / hr, the drum speed to 120 r / min, and the receiving distance to 15 cm.
[0071] (4) The prepared raw fibers were cross-linked and cured at 250 °C for 2 h. The cured polymer fibers were then placed in a vacuum box atmosphere furnace and heated to 800 °C at a heating rate of 5 °C / min in a nitrogen atmosphere and kept at this temperature for 1 h.
[0072] Example 5
[0073] The silicon carbide ceramic fiber containing hafnium element is prepared according to the following steps:
[0074] (1) Dissolve 10 g of solid PCS in 50 g of tetrahydrofuran (THF) and stir thoroughly with a magnetic stirrer for 2 h until the liquid is clear. Add 2.5 g of hafnium acetylacetonate (Hf(acac)4) to the above transparent mixed solution and stir magnetically at room temperature for 2 h until it is completely dissolved.
[0075] (2) At room temperature, add 3.5 g of cellulose acetate to the solution prepared in step (1) and stir for 2 h until the solution becomes clear to obtain a spinning solution.
[0076] (3) The mixed spinning solution prepared in step (2) is sucked into a syringe and placed on an electrospinning machine. The voltage of the electrospinning machine is set to 15 kV, the flow rate to 3 mL / hr, the drum speed to 120 r / min, and the receiving distance to 15 cm.
[0077] (4) The prepared raw fibers were cross-linked and cured at 240 °C for 2 h. The cured polymer fibers were then placed in a vacuum box atmosphere furnace and heated to 1000 °C at a heating rate of 5 °C / min in a nitrogen atmosphere and kept at this temperature for 1 h.
[0078] Example 6
[0079] The silicon carbide ceramic fiber containing hafnium element is prepared according to the following steps:
[0080] (1) Dissolve 10 g of solid PCS in 50 g of tetrahydrofuran (THF) and stir thoroughly with a magnetic stirrer for 2 h until the liquid is clear. Add 2.5 g of hafnium acetylacetonate (Hf(acac)4) to the above transparent mixed solution and stir magnetically at room temperature for 2 h until it is completely dissolved.
[0081] (2) At room temperature, add 3.5 g of cellulose acetate to the solution prepared in step (1) and stir for 2 h until the solution becomes clear to obtain a spinning solution.
[0082] (3) The mixed spinning solution prepared in step (2) is sucked into a syringe and placed on an electrospinning machine. The voltage of the electrospinning machine is set to 11 kV, the flow rate to 3 mL / hr, the drum speed to 120 r / min, and the receiving distance to 15 cm.
[0083] (4) The prepared raw fibers were cross-linked and cured at 260 °C for 2 h. The cured polymer fibers were then placed in a vacuum box atmosphere furnace and heated to 1200 °C at a heating rate of 5 °C / min in a nitrogen atmosphere and kept at this temperature for 1 h.
[0084] Example 7
[0085] The silicon carbide ceramic fiber containing hafnium element is prepared according to the following steps:
[0086] (1) Dissolve 10 g of solid PCS in 50 g of tetrahydrofuran (THF) and stir thoroughly with a magnetic stirrer for 2 h until the liquid is clear. Add 2.5 g of hafnium acetylacetonate (Hf(acac)4) to the above transparent mixed solution and stir magnetically at room temperature for 2 h until it is completely dissolved.
[0087] (2) At room temperature, add 3.5 g of cellulose acetate to the solution prepared in step (1) and stir for 2 h until the solution becomes clear to obtain a spinning solution.
[0088] (3) The mixed spinning solution prepared in step (2) is sucked into a syringe and placed on an electrospinning machine. The voltage of the electrospinning machine is set to 11 kV, the flow rate to 3 mL / hr, the drum speed to 120 r / min, and the receiving distance to 15 cm.
[0089] (4) The prepared raw fibers were cross-linked and cured at 250 °C for 2 h. The cured polymer fibers were then placed in a vacuum box atmosphere furnace and heated to 1400 °C at a heating rate of 5 °C / min in a nitrogen atmosphere and kept at this temperature for 1 h.
[0090] Comparative Example 1
[0091] Pure PCS polymer fibers were prepared by following the steps below:
[0092] (1) Dissolve 10 g of solid PCS in 50 g of tetrahydrofuran (THF) and stir the mixture thoroughly with a magnetic stirrer for 2 h until the liquid becomes clear.
[0093] (2) At room temperature, add 3.5 g of cellulose acetate to the solution prepared in step (1) and stir for 2 h until the solution becomes clear to obtain a spinning solution.
[0094] (3) The mixed spinning solution prepared in step (2) is sucked into a syringe and placed on an electrospinning machine. The voltage of the electrospinning machine is set to 15 kV, the flow rate to 3 mL / hr, the drum speed to 120 r / min, and the receiving distance to 15 cm.
[0095] (4) The prepared fibrils were cross-linked and cured at 250 °C for 2 h.
[0096] The elastic recovery rates of the ceramic fibers obtained in the above-mentioned Examples 1-7 and Comparative Example 1 when compressed by 50% were tested, and the results are shown in Table 1 below.
[0097] Table 1
[0098]
[0099] It can be seen from Table 1 that the ceramic fiber of the present invention has excellent resilience. Among them, the elastic recovery rate of the ceramic fibers prepared in Examples 6 and 7 when compressed by 50% is as high as 97%-99%, indicating that the ceramic fiber of the present invention has excellent mechanical properties and has good application prospects in high-temperature structural parts, aerospace and other fields.
[0100] Performance test results:
[0101] The morphology of the samples in Examples 1 to 3 was analyzed using a JSM-7800F field emission scanning electron microscope. Figure 2 (ac) It can be seen that when the content of hafnium acetylacetonate is 5% and 7% of the mass fraction of tetrahydrofuran, the fiber morphology is good and the thickness is relatively uniform, indicating that the hafnium acetylacetonate is evenly dispersed in the solution. The addition of metal interacts with the magnetic field, and the magnetic field force on the solution is better, making the spun silk more uniform. However, when the content of hafnium acetylacetonate is 10% of the mass fraction of tetrahydrofuran, the obtained fiber is cohesive and many beads appear. This may be because the content of hafnium acetylacetonate is too high, and they agglomerate with each other, and cannot be fully mixed with the solution and then compatible, forming more beads.
[0102] The morphology of the samples in Example 7 was analyzed using a JSM-7800F field emission scanning electron microscope. Figure 3 As shown in the figure, when the sintering temperature is 1400℃, the fiber presents a flat structure with basically uniform thickness and relatively even distribution. There is no breakage or destructive change in morphology due to high temperature, and a good morphology is maintained. It can be seen that SiC fiber containing Hf element has good high temperature resistance and can maintain structural stability under extreme temperature conditions.
[0103] Thermo's Fourier transform infrared spectrometer (FTIR, 380 Nicolet) was used to analyze whether hafnium acetylacetonate was successfully added to the PCS fiber. Figure 4 The following are Fourier transform infrared spectra of the polymer fiber and hafnium acetylacetonate (Hf(acac)4) prepared in Example 1 and Comparative Example 1 of the present invention. Figure 4 As shown in the figure, the infrared spectrum of pure PCS fiber shows an absorption band attributed to CH (2950-2900 cm -1 ), Si-H(2100 cm -1 ), Si-CH3(1250 cm -1 )、Si-C(830 cm -1 )、C=C(1531 cm -1 The infrared absorption bands of hafnium acetylacetonate are CH (2950-2900 cm -1)、C=O(1650 cm -1 )、C=C(1531 cm -1 )、Hf-OC(1022 cm -1 )、Hf-O(770 cm -1 、647 cm -1 The infrared absorption band displayed by PCS fiber containing hafnium acetylacetonate is attributed to CH (2950-2900 cm -1 )、Si-H(2100 cm -1 )、C=O(1650 cm -1 )、C=C(1531 cm -1 )、Si-CH3(1250 cm -1 )、Hf-OC(1022 cm -1 )、Hf-O(770 cm -1 、647 cm -1 )、Si-O-Hf(959 cm -1 )、Si-C(830 cm -1 ). 1292 cm -1 The peaks at 1570-1500 cm correspond to the stretching vibration of C-CH3 and the in-plane bending vibration of CH of the acetylacetonate ligand. -1 Several weak peaks appear in the range corresponding to Hf-OH stretching vibrations, which is the result of partial replacement of Hf-OC bonds by Hf-OH bonds during the hydrolysis reaction. The infrared absorption peaks of the fibers prepared in Example 1 have infrared absorption bands common to both Hf(acac)4 and pure PCS fibers, indicating that hafnium acetylacetonate has been successfully added to PCS fibers.
[0104] X-ray diffraction was used to investigate the effect of high temperature sintering temperature on the structure of ceramic fibers, such as Figure 5It is the XRD diagram of the ceramic fiber prepared in Examples 1 and 5-7. When the fiber is cured at 250°C without high-temperature sintering, no obvious peak appears. This is because after curing at 250°C, the fiber is not converted into ceramic fiber and is in an amorphous state. When the sintering temperature is 1000°C, SiC peaks appear at around 2θ=35°, 60°, and 73°, and HfO2 peaks appear at around 2θ=30° and 50°. When the temperature is above 1000°C, sharp peaks appear in the figure, indicating that the sintering temperature has reached the fiber ceramic conversion temperature, and the Si provided by the solid PCS begins to carbonize to form the peak of SiC, while hafnium acetylacetonate is oxidized to form the peak of HfO2. A new SiO2 peak appeared at 1200℃, which proves that Si was oxidized to form the SiO2 peak at 1200℃. It can be seen that Si was first carbonized and then oxidized. The reason may be that hafnium acetylacetonate gradually precipitated and wrapped around the fiber during the sintering process, and more oxygen reacted with hafnium acetylacetonate first and then with Si. When the sintering temperature reached 1400℃, the diffraction peak became sharper, the ceramicization process became more intense, hafnium acetylacetonate was carbonized to form a new HfC peak, and the peak of HfSiO4 gradually appeared.
[0105] The ceramic fiber prepared in Example 7 was characterized by transmission electron microscopy, and the distribution of the contained elements Si, O, Hf, and C was described in combination with EDS element distribution analysis. Figure 6 (ad) It can be seen that the elements are evenly distributed on the fiber structure, and oxygen is mainly present on the fiber surface. Figure 6 (e) The TEM low-magnification morphology image of the fiber after pyrolysis at 1400 °C shows that the fiber still maintains its original morphology after pyrolysis without any change. Figure 6(f) A clear lattice structure can be seen. In the figure, the interplanar spacing of 0.24 nm corresponds to the (311) plane of the SiC crystal phase, the interplanar spacing of 0.26 nm corresponds to the (422) plane of the SiO2 lattice, and the interplanar spacings of 0.15 nm, 0.23 nm, and 0.33 nm correspond to the (113) plane of HfO2, the (200) plane of HfC, and the (200) plane of HfSiO4, respectively. This proves the presence of SiC, SiO2, HfO2, HfC, and HfSiO4 in the Hf / SiC-1400 fiber. Combined with EDS element distribution analysis and lattice measurement and verification, it can be seen that the oxides inside the material are mainly HfO2, HfSiO4 and SiO2 and are mainly distributed on the periphery of the material. It can be seen that the introduction of Hf element can promote the formation of surface SiO2 on the one hand, so that a SiO2 protective film is formed on the surface; on the other hand, the HfO2 and HfSiO4 generated by its own oxidation can effectively block the inward diffusion of O, reducing the probability of oxidation of the internal SiC matrix. It can be seen that the generation of HfC is conducive to improving the material's antioxidant properties, inhibiting the growth of SiC grains, and reducing the probability of large cracks in the fiber. It can also be seen from the TEM image that a large number of microcrystalline structures are wrapped in the peripheral amorphous matrix, forming a large number of amorphous boundaries. The existence of amorphous boundaries better protects the matrix and improves the material's antioxidant and high temperature resistance.
[0106] In order to further study the oxidation resistance of hafnium-containing fibers, the ceramic fibers of Example 7 were sintered at 1600° C. in an air atmosphere furnace, and then subjected to XRD analysis. Figure 7 As shown. Figure 7 It can be seen that the number of SiO2 and HfO2 peaks in the oxidized ceramic fiber increases significantly and becomes sharper. In addition, the HfSiO4 peak is also more obvious. This is mainly because the Si and Hf elements in the fiber can react with more oxygen in the air atmosphere to produce more oxides, which is reflected in the XRD diagram as the oxide peaks are more obvious.
[0107] The thermal stability of the samples was analyzed using a thermogravimetric analyzer (TG / DTA, Q600). Figure 8 (a) is the thermogravimetric curve of the fiber prepared in Example 1 of the present invention and Comparative Example 1. Figure 8As shown in (a), the weight loss rate is extremely low at 0℃~300℃, mainly due to the evaporation of the unevaporated solvent inside the fiber and the dehydrogenation reaction and evaporation of low molecular weight substances. The weight loss is mainly concentrated at 300℃~1000℃. The main reactions in this process are the rearrangement of Si-C bonds and Hf-O bonds and the volatilization of organic groups such as methyl, ethyl and phenyl. The mass loss is not large at 1000℃~1200℃, indicating the transformation of polymer to ceramic. When the temperature exceeds 1400℃, the curve tends to be stable and the weight loss rate is almost unchanged, indicating that the ceramicization is completed. When the temperature is as high as 1600℃, the weight loss rate of hafnium-containing fiber is only less than 20%. It can be seen that compared with pure PCS fiber, the weight loss rate of hafnium-containing fiber is significantly lower than that of pure PCS fiber, indicating that the high temperature resistance of hafnium-containing fiber is better. The thermal conductivity of the sample was tested using a thermal conductivity meter (TC 3000E, XIA TECH, CHN). Figure 8 (b) is a histogram of the thermal conductivity of the ceramic fibers prepared in Examples 4-7 of the present invention. Figure 8 (b) It can be seen that as the temperature increases, the thermal conductivity of the fiber gradually decreases. This is mainly because as the temperature increases, the finer the fiber diameter, the smaller the pore size, the greater the resistance to heat transfer, resulting in a decrease in thermal conductivity. Although the thermal conductivity increases when the temperature rises to 1400 °C, the fiber generally maintains a fluffy structure, and the gaps between the fibers are filled with air, so its thermal conductivity does not change much and is at a low state.
[0108] Although the preferred embodiments of the present invention are described above, the present invention is not limited to the above-mentioned specific embodiments. The above-mentioned specific embodiments are merely illustrative and not restrictive. Under the guidance of the present invention, ordinary technicians in this field can also make many forms of specific changes without departing from the scope of protection of the invention spirit and claims, which all fall within the scope of protection of the present invention.
Claims
1. A method for preparing a flat high-elasticity high-temperature thermal insulation ceramic fiber, characterized in that: include: (1) dissolving polycarbosilane powder in tetrahydrofuran and stirring evenly, and then adding hafnium acetylacetonate to prepare a precursor solution; wherein the mass ratio of the polycarbosilane powder to the tetrahydrofuran is 2:(8-10), and the mass fraction of the hafnium acetylacetonate to the tetrahydrofuran is 5%-7%; (2) adding a spinning aid cellulose acetate to the precursor solution to obtain an electrospinning solution; (3) placing the electrospinning solution on an electrospinning machine for electrospinning to obtain nanofibers; (4) After the nanofibers are cross-linked and solidified, they are calcined in a vacuum atmosphere or an inert atmosphere to remove organic components to obtain flat ceramic fibers.
2. The method for preparing a flat high-elastic high-temperature thermal insulation ceramic fiber according to claim 1, characterized in that: The stirring time of dissolving the polycarbosilane powder in the tetrahydrofuran in step (1) is 2 to 4 hours.
3. The method for preparing a flat high-elasticity high-temperature thermal insulation ceramic fiber according to claim 1, characterized in that: The stirring time of adding the hafnium acetylacetonate to obtain the precursor solution in step (1) is 1 to 5 hours.
4. The method for preparing a flat high-elasticity high-temperature thermal insulation ceramic fiber according to claim 1, characterized in that: The mass ratio of the cellulose acetate in step (2) to the tetrahydrofuran in step (1) is (5-7):100, and the stirring time of adding the spinning aid cellulose acetate to the precursor solution to obtain the electrospinning solution is 2-3 h.
5. The method for preparing a flat high-elasticity high-temperature thermal insulation ceramic fiber according to claim 1, characterized in that: The process parameters of the electrospinning in step (3) include: voltage of 10-20 kV, drum speed of 80-150 rpm, receiving distance of 15-20 cm, and feeding speed of 1-5 mL / h.
6. The method for preparing a flat high-elasticity high-temperature thermal insulation ceramic fiber according to claim 1, characterized in that: The cross-linking curing in step (4) is reacted at 240-260° C. for 1-2 h.
7. The method for preparing a flat high-elasticity high-temperature thermal insulation ceramic fiber according to claim 6, characterized in that: The heating rate of the cross-linking curing is 1 to 5°C / min.
8. The method for preparing a flat high-elasticity high-temperature thermal insulation ceramic fiber according to claim 1, characterized in that: The calcination in step (4) is to heat to 1200°C to 1400°C and then keep warm for 1 to 2 hours.
9. The method for preparing a flat high-elasticity high-temperature thermal insulation ceramic fiber according to claim 8, characterized in that: The heating rate of the calcination is 4 to 6 °C / min.
10. A flat high-elastic high-temperature thermal insulation ceramic fiber, characterized in that: Obtained by the preparation method according to any one of claims 1 to 9.
Citation Information
Patent Citations
Preparation method of MC-SiC ultrahigh-temperature ceramic fibers
CN105732041A
Flexible hafnium carbide / silicon carbide composite nano fiber membrane with electromagnetic wave absorption performance and preparation method thereof
CN108866810A
Sol-gel preparing and spinning method of ultrafine continuous alumina fibers
CN110922170A
Hafnium oxide fiber, preparation method thereof and application of hafnium oxide fiber in antioxidant coating
CN112010656A
Lightweight bearing nano ceramic aerogel based on electrospinning method and preparation method thereof
CN114751761A